2013
DOI: 10.1159/000351109
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Signaling Pathways in Uteri of Rats with Endometrial Hyperplasia Induced by Ovariectomy Combined with Estrogen

Abstract: Aims: To explore a new reliable method inducing an animal model similar to the morphology and apoptotic signaling pathways in endometrial hyperplasia patients. Methods: After the rats were ovariectomized, estradiol benzoate (60 µg/​100 g) was intramuscularly injected on alternate days for 4 weeks. The morphology in the uterus was observed under a light microscope and by electron microscopy. The expression levels of survivin/caspase-3 and Fas/FasL were checked by immunohistochemistry, Western blotting and real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…In our study, treatment with EB showed significant decrease in caspase‐3 immunoexpression compared to control group. These findings are in agreement with He et al and Guo et al .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In our study, treatment with EB showed significant decrease in caspase‐3 immunoexpression compared to control group. These findings are in agreement with He et al and Guo et al .…”
Section: Discussionsupporting
confidence: 94%
“… Group I was received vehicle of DIA (1% carboxymethylcellulose) and intramuscular (im) olive oil three times per week for 4 weeks . Group II was treated with DIA (50 mg/kg/day orally) and im olive oil 3 times per week for 4 weeks . Group III was treated with vehicle of DIA (1% carboxymethylcellulose) and im injection of EB (60 μg/100 g) three times per week for 4 weeks . Group IV was treated with DIA (50 mg/kg/day orally) + im injection of EB (60 μg/100 g) three times per week for 4 weeks . …”
Section: Methodsmentioning
confidence: 99%
“…An association between obesity and EC is well recognized and is explained by unregulated estrogen expression [24,25]. An elevated BMI was significantly related to the presence of EC in ACH patients [26].…”
Section: Discussionmentioning
confidence: 99%
“…Survivin, a potent inhibitor of apoptosis, plays an essential role in EH [ 43 , 44 ]. He et al [ 44 ] reported an increase in survivin in EB-induced EH, which is in line with the present study results.…”
Section: Discussionmentioning
confidence: 99%
“…Survivin, a potent inhibitor of apoptosis, plays an essential role in EH [ 43 , 44 ]. He et al [ 44 ] reported an increase in survivin in EB-induced EH, which is in line with the present study results. On the other hand, survivin was significantly lower in the EH+IRB group compared to the EH group.…”
Section: Discussionmentioning
confidence: 99%